Presumption of Innocence as a Legal Fiction: Philosophical Foundations and Practical Implications in the Criminal Justice System - Vincent Patria Setyawan (Activa Yuris: Jurnal Hukum, 2026)
The principle of the presumption of innocence is a fundamental doctrine in criminal law that guarantees every individual the right to be treated as innocent until proven guilty by a competent court. However, in practice, this principle often faces significant challenges, especially when it is confronted with public opinion, media exposure, and institutional interests. This study critically examines the presumption of innocence as a legal fiction, exploring both its philosophical foundations and its practical application within the criminal justice system. The objective of this research is to analyze how the legal fiction of presumed innocence functions as a normative ideal, while also identifying the gaps between theoretical guarantees and their actual implementation in legal processes. The research method used in this study is normative legal analysis, supported by a conceptual and philosophical approach. Primary and secondary legal materials are examined to understand how legal fiction is constructed and justified in criminal law theory. The results of this study show that the presumption of innocence, although formally enshrined in legal instruments, is often undermined in practice by pre-trial public exposure, institutional bias, and procedural irregularities. This condition weakens the role of legal fiction as a protective mechanism for suspects and defendants. The conclusion of this study emphasizes the need for a more consistent application of the presumption of innocence, not only as a formal principle but as a substantive guarantee of fairness and justice. Legal fiction must be critically evaluated to ensure that it does not merely serve as rhetorical ornamentation but becomes an effective tool in upholding human dignity within the criminal justice system.